"Malignant Mesenchymoma" Revisited: A Clinicopathologic Study of Leiomyosarcomas With Osteosarcomatous Differentiation. (13th October 2022) - Yu, Sanhong; Hornick, Jason L.
Abstract : Leiomyosarcoma (LMS) is the most common sarcoma in adults. Rarely, LMS dedifferentiates into an undifferentiated sarcoma. Very few cases of LMS with heterologous osteosarcomatous differentiation (OS) have been reported. The purpose of this study was to evaluate the clinicopathologic features of LMS with OS. Of 5570 LMS cases diagnosed from 2006 to 2022, 15 cases (0.2%) of LMS with OS were identified, affecting 13 females and 2 males; ages ranged from 32 to 66 years (median: 53 y). Ten tumors arose in the uterus, 2 in the retroperitoneum, and 1 each in the mesentery, mediastinum, and rectum. Primary tumors ranged from 7 to 20 cm (mean: 16 cm). The LMS components showed conventional spindle cell morphology in most cases; 3 cases showed marked pleomorphism; 3 cases contained an epithelioid component; and 1 case showed myxoid features. In 5 cases OS was identified in the primary tumor, whereas in 10 cases OS was first detected in metastases. One metastatic and 2 primary LMS showed both OS and chondrosarcomatous differentiation. Prominent osteoclastic giant cells were seen in the OS components in 11 cases. Mitotic activity ranged from 17 to 61/10 HPF with tumor necrosis in 10 cases. Twelve patients developed metastases; sites included lungs, diaphragm, kidney, adrenal glands, colon, small intestine, liver, bone, and pancreas. At last follow-up, 8 patients had died of disease, and 4 patients were alive with metastases. The interval between OS and death ranged from 3 weeks to 18 months (median: 6.5 mo). Development of OS in LMS is exceptionally rare. This form of heterologous differentiation may occur in both primary tumors and metastases. LMS with OS is highly aggressive with poor outcomes. Awareness of this phenomenon is important to avoid misdiagnosis as osteosarcoma.